723. Validation of a Wild-Type Influenza A/Texas-Like H3N2 Human Challenge Model with Comparison to the Validated A(H1N1)pdm09 Model. (26th November 2018) - Han, Alison; Czajkowski, Lindsay; Donaldson, Amanda; Baus, Holly Ann; Reed, Susan; Athota, Rani; Bristol, Tyler; Rosas, Luz Angela; Cervantes-Medina, Adriana; Taubenberger, Jeffery K; Memoli, Matthew J
Abstract: Background: Healthy volunteer challenge studies provide an opportunity to better understand influenza pathogenesis and correlates of protection. The development of vaccines and therapeutics has relied on these studies as will future universal vaccine candidates. The first fully validated wild-type human infection model with A(H1N1)pdm09 was developed at the NIH Clinical Center (CC) in 2012 and this study represents the first validation of a wild-type seasonal H3N2 human infection model. The objective of this study was to characterize a wild-type Influenza A/Texas-like H3N2 challenge virus in healthy volunteers. Methods: Healthy volunteers were isolated at the NIH CC for a minimum of 9 days. Subjects received a single dose of a reverse genetics, cell-based, GMP, wild-type A H3N2 virus intranasally. Dose escalation was performed from 10 4 to 10 7 TCID50 . Viral shedding and clinical disease were evaluated daily, including clinician assessments and a validated patient-reported outcome tool, FLU-PRO©. Results: A total of 37 subjects were challenged. Sixteen (43%) subjects had viral shedding and 27 (73%) developed influenza symptoms, with 12 subjects (32%) experiencing mild-to-moderate influenza disease (MMID) defined as symptoms and shedding. Only subjects receiving the 10 6 and 10 7 TCID50 doses experienced MMID at 44% and 40%, respectively. Nose and throat symptoms were most common and peaked by Days 2–3 post-challenge. Although serum antibody responses were observed, many of these responses were limited in a significant number of subjects. Conclusion: The A/Texas-like H3N2 Influenza challenge virus safely induced MMID in healthy volunteers, but was less effective than the A(H1N1)pdm09 challenge virus. This lower MMID rate of 40% was observed at the 10 7 TCID50 dose and was driven by less detection of shedding as the incidence of symptoms was similar to A(H1N1)pdm09. The limited serum antibody responses observed demonstrate that preexisting immunity in healthy volunteers against the seasonal H3N2 lineage may limit shedding compared with the more recently emerged seasonal A(H1N1)pdm09 lineage. The successful characterization of this H3N2 model makes future studies using this model to explore viral pathogenesis or evaluate vaccines possible. This research was supported by the Intramural Research Program of the NIH, NIAID. Disclosures: All authors: No reported disclosures.